Domestique living (storage system for mountain bikes) - Nievera, Ronald Jose Panlilio; Mayo, Adelaida Villaraza (1996.)
Biking is a popular competitive and fitness activity. Mountain
Biking is a popular competitive and fitness activity. Mountain Biking, its most recent variant, is one of the fastest growing sports today and its enthusiasts have grown dramatically in only a few years after its introduction. For one reason or another, a certain group of mountain bikers prefer to store their bicycles inside their rooms. This arrangement demands certain factors to be considered in order for the mountain bike to be stored efficiently inside the room. The qualities of a good storage system for storing a mountain bike inside rooms are the following: 1. Ease of storage and retrieval of the bicycle storage ares- it should minimize the need or effort in lifting the bicycle on and off the storage system and also the use of numerous actions in storing and retrieving it. 2. Efficient placement of the storage- it should minimize the length of travel from the storage area to the entry of the room. 3. Preservation of the interior- it should minimize the contact of the bicycle with the parts of the interior to prevent the deterioration of the room. 4. Provisions for maintenance- the storage system should provide access for minor repairs and maintenance even without removing the bicycle from the storage area. 5. Storage of gear and equipment- the design should also include storage provisions for the bikers other gear and equipment.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Domestiques (Bicycle racing) -- Philippines; Storage facilities -- Philippines